Kinetics of inhaled antibodies by gamma scintigraphy - Pereira, Catherine (2013)
Inhalation represents a potentially attractive delivery route for biologics, especially those designed to treat pulmonary diseases such as asthma, cystic fibrosis or lung cancer. Delivery directly to the site of action should increase local concentrations of drug, whilst reducing systemic side effects. However, there is limited knowledge regarding the mechanisms of pulmonary clearance, with gaps in understanding; where molecules are absorbed, the mechanisms involved, regional variability throughout the lung, and how to control pulmonary retention and/or facilitate cellular uptake.